Interaction of Microplastics and Heavy Metals on Aquatic Organisms : A Review - Putri, Adinda Kurnia; Ekalaturrahmah, Yenni Arista Cipta; Ahmad, Ahmad; Soheh, Moh (Institute for Research and Community Service (LPPM), Universitas Islam Madura, Indonesia, 2025)
Microplastics, which originate from a variety of sources and are widespread in aquatic ecosystems, have a significant capacity to adsorb heavy metals through a variety of physicochemical mechanisms, including electrostatic interactions, complex formation, ion exchange, and surface precipitation. A systematic review was used in this study of 50 published articles on the interactions of microplastics and heavy metals on aquatic organisms. The characteristics of microplastics (size, shape, type of polymer) and environmental conditions (pH, salinity, dissolved organic matter) greatly influence the adsorption efficiency and behavior of microplastics in the aquatic environment. Once inside the organism through direct consumption, gills, cuticle penetration, or cellular translocation, microplastics can release adsorbed heavy metals, creating effects that increase the bioavailability and toxicity of the metal. Biological responses that occur include oxidative stress, DNA damage, disruption of the antioxidant defense system, histopathological changes in tissues and organs, growth and reproductive disorders, and behavioral changes. At the population and ecosystem level, microplastic-heavy metal interactions can lead to shifts in community composition, disruption of food webs, changes in biogeochemical cycles, and degradation of ecosystem services.